Огляд статті - Шмігер, Тарас (Східноєвропейський журнал психолінгвістики, 2017)
James W. Underhill. Voice and Versification in Translating Poems. University of Ottawa Press, 2016. xiii, 333 p.After its very strong stance in the 19th century, the versification part of translation scholarship was gradually declining during the 20th century, substituted by the innovative searches for semasiology, culture and society in text. The studies of structural and cognitive approaches to writing, its postcolonial identity or gender-based essence uncovered a lot of issues of the informational essence of texts, but overshadowed the meaning of their formal structures. The book ‘Voice and Versification in Translating Poems’ welcomes us to the reconsideration of what formal structures in poetry can mean.James William Underhill, a native of Scotland and a graduate of Hull University, got Master’s and PhD degrees from Université de Paris VIII (1994 and 1999 respectively). He has translated from French, German and Czech into English, and now, he is full professor of poetics and translation at the English Department of Rouen University as well as the director of the Rouen Ethnolinguistics Project. His scholarly activities focused on the subject of metaphor, versification, cultural linguistics and translation. He also authored ‘Humboldt, Worldview, and Language’ (Edinburgh University Press, 2009), ‘Creating Worldviews: Ideology, Metaphor and Language’ (Edinburgh University Press, 2011), and ‘Ethnolinguistics and Cultural Concepts: Truth, Love, Hate and War’ (Cambridge University Press, 2012).the belief of the impossibility of translating poems, poems are translated and sometimes translated quite successfully. In contemporary literary criticism, one observes the contradiction that despiteJames W. Underhill investigates this fascinating observable fact by deploying the theory of voice.The first part of the book, ‘Versification’, is more theoretical as the researcher is to summarizes the existing views and introduce fundamental terms and guidelines. The book is strongly influenced by the French theoretician Henri Meschonnic, but other academic traditions of researching verse are also present. This part includes four chapters where the author discusses recent scholarship in the subject-matter (‘Form’), theories of verse structure (‘Comparative Versification’), rhythm and stress systems (‘Meter and Language’), and the issues of patterning and repetition (‘Beyond Metrics’). The author shapes the key principle of his views that ‘[v]oice represents the lyrical subject of the poem, the “I” that creates it, but that is also created in and by the poem’ (p. 44). This stipulation drives him to the analysis of five facets in poetry translation: 1) the voice of a language; 2) the voice of an era; 3) the voice of a literary movement or context of influence; 4) the voice of a poet; 5) the voice of the particular poem.Part 2, ‘Form and Meaning in Poetry Translation’, offers more theorizing on how we can (or should) translate form. The triple typology of main approaches – (translating form blindly; translating a poem with a poem; translating form meaningfully) – sounds like a truism. The generic approach might be more beneficial, as the variety of terms applied in poetry translation and applicable to the idea of the book – (poetic transfusion, adaptation, version, variant) – would widen and deepen the range of questions trying to disclose the magic of transformations while rendering poetry of a source author and culture to the target reader as an individual and a community. The experience of a reader (individual and cultural personality) could be a verifying criterion for translating strategies shaped the translator’s experience.In Part 3, ‘Case Studies’, the author explores the English translations of Charles Baudelaire’s poetry and the French and German translations of Emily Dickinson’s poems. All translations theoreticians and practitioners will agree with the researcher’s statement that “[t]ranslating that simplicity is inevitably arduous” (p. 187). Balancing between slavery-like formalist operations and free transcreations, translators experiment on strategies of how to reproduce the original author’s voice and versification successfully enough. The longing categorically pushes us to the necessity of understanding what is in language but communication, how a nation’s emotionality is built linguistically, and why a language applies certain meters for specific emotional articulation.‘Glossary’ (p. 297-319), compiled on the basis of theoretical reflections in the main text on the book, is of significant practical value. This could really become a good sample to follow in any academic book.This book takes us closer to the questions ‘How can a form mean something?’ and ‘How can we verify this meaning?’, though further research merged in ethnolingual, ethnopoetic and ethnomusical studies still promises to be extremely rich.